The Effect of Temperature, Stirring, and Contact Time on Reducing Chemical Oxygen Demand (COD) Levels of Palm Oil Mill Effluent (POME) Using Cocoa Peels Adsorbent (Theobroma cacao L.) - Firstin Rizki Annisa Hasibuan; Fajar Indah Puspita Sari; Occa Roanisca (Department of Chemistry - Universitas Bangka Belitung, 2023)
Cocoa peels (Theobroma cacao L.) are one of the plantation wastes that haven’t been used optimally. The content of cocoa peels makes the peels potential to be used as an adsorbent to reduce COD levels of POME. POME is liquid waste from the processing palm oil industry. This study was aimed to determine the characteristics of the cocoa peels adsorbent and the effectiveness of using cocoa peels adsorbent in reducing COD levels of POME. The powder was activated using nitric acid to increase the surface area of the adsorbent. The cocoa peels adsorbent was further characterized to determination water and ash content, FTIR analysis, and SAA. Cocoa peels adsorbent contains 10.40% moisture and 4.08% ash. FTIR analysis showed the presence of groups O–H, C–H, C=C, C–O– C, C–O, C–NO2 on the adsorbent of cocoa peels. The surface area of the adsorbent cocoa peel increased after activation from 3.48071 m2/g to 3.93845 m2 /g. The method used to test the content COD of POME is closed reflux titrimetrically. Adsorpstion process used variation like temperature, stirring speed, and contact time. The best reduction was obtained at 30oC with a stirring speed of 600 rpm at 120 minutes contact time, with 76.19% removal percentage for COD.